Preparation method of high-performance titanium dioxide film
By using specific chemical substances to prepare TiO2 sol and using spin coating to form a film on the silicon wafer, the existing titanium dioxide thin film has solved the problems of low piezoelectric constant, poor catalytic performance and complex preparation process, achieving high performance, stable and economical Preparation of titanium dioxide film.
Patent Information
- Application Number
- CN202411556489.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-11
AI Technical Summary
The existing titanium dioxide film has a low piezoelectric constant, poor catalytic performance, complex preparation process and high cost, and weak bonding force between the film and the substrate, which limits its potential in piezoelectric and catalytic applications.
TiO2 sol is prepared by materials such as tetrabutyl titanate, anhydrous ethanol, deionized water, glacial acetic acid, nitric acid and sodium 1-octane sulfonate, and TiO2 is formed on P-type (100) crystalline silicon wafer by spin coating. The film is annealed to improve the stability and bonding strength of the film.
The prepared titanium dioxide thin film has strong physical and chemical stability, high piezoelectric constant, outstanding catalytic performance, simple preparation process and low cost, and the film is closely integrated with the substrate. It is suitable for sensors, environmental pollution control and artificial intelligence fields.
Smart Images

Figure CN119409523A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of film preparation, and in particular relates to a high-performance titanium dioxide film and a preparation method thereof. Background Art
[0002] With the development of science and technology, semiconductor catalytic materials have broad application prospects in the fields of environmental pollution control, sensors and artificial intelligence. The lead element contained in traditional semiconductor catalytic materials (PZT) poses a serious threat to the brains of animals and humans, and does not meet the current requirements for environmentally friendly materials. The piezoelectric and catalytic properties of the materials currently being widely studied will fail or significantly reduce under high temperature and high pressure environments, limiting their scope of application. In addition, these materials are costly, have complex preparation processes, and have mediocre performance, making them difficult to industrialize. Titanium dioxide has become an ideal material in the fields of sensors, environmental pollution control and artificial intelligence because of its stable chemical properties, non-toxicity, and ability to effectively remove pollutants from the atmosphere and water. However, the piezoelectric properties of traditional titanium dioxide materials are relatively weak, limiting their potential in piezoelectric applications. Summary of the invention
[0003] The purpose of the present invention is to solve the problems of low piezoelectric constant, poor catalytic performance, high requirements for preparation process and weak bonding between the film and the substrate of the existing titanium dioxide film, and to provide a method for preparing a titanium dioxide film with strong physical and chemical stability, close bonding with the substrate, high piezoelectric constant and outstanding catalytic performance, while reducing the preparation cost to meet application requirements.
[0004] The method for preparing a high-performance titanium dioxide film provided by the present invention comprises the following steps:
[0005] Step 1: Preparation of TiO2 sol
[0006] Tetrabutyl titanate and anhydrous ethanol are mixed evenly, and solution A is obtained after magnetic stirring; deionized water, glacial acetic acid and nitric acid are mixed, sodium 1-octane sulfonate is added and solution B is obtained after magnetic stirring; solution B is dripped into solution A drop by drop, stirred evenly, and TiO2 sol is obtained.
[0007] Step 2: Preparation of TiO2 thin film
[0008] The P-type (100) silicon wafer is ultrasonically cleaned in deionized water and anhydrous ethanol in turn and then dried. The TiO2 sol obtained in step 1 is spin-coated on the silicon wafer. After drying, the spin coating is repeated 3 to 5 times. The spin-coated silicon wafer is annealed to obtain a TiO2 film based on the silicon wafer.
[0009] In the above step 1, the volume ratio of tetrabutyl titanate, anhydrous ethanol, deionized water, glacial acetic acid and nitric acid is preferably 1:1.5-2:1.5-2:0.5-1:0.1-0.2.
[0010] In the above step 1, the mass-volume ratio of the sodium 1-octane sulfonate to tetrabutyl titanate is preferably 0.15-0.3 g:1 mL.
[0011] In the above step 2, the drying treatment temperature is preferably 150-180° C., and the drying time is 20-60 min.
[0012] In the above step 2, the spin coating is firstly carried out at a rotation speed of 300 to 500 rpm for 10 to 20 s, and then at a rotation speed of 2500 to 3500 rpm for 20 to 30 s.
[0013] In the above step 2, the annealing treatment temperature is preferably 800-900° C., and the annealing time is 60-90 min.
[0014] The beneficial effects of the present invention are as follows:
[0015] 1. In the process of preparing TiO2 sol, the anionic surfactant sodium 1-octane sulfonate is added. Due to its good surface activity, it is adsorbed on the surface of the colloidal particles, increasing the repulsive force between the colloidal particles, thereby preventing the colloidal particles from aggregating and settling, and improving the stability of the colloid.
[0016] 2. The substrate of the present invention is a P-type (100) crystal face silicon wafer, because it has a higher carrier (electron and hole) mobility, which improves the conductivity of the material; its structure has higher flatness and consistency of lattice parameters, which improves the repeatability of the preparation process; it has good matching and compatibility, and can match many commonly used semiconductor materials and stacked structures.
[0017] 3. The present invention adopts a spin coating method to prepare a thin film, which is simple to operate, does not require complex equipment and high temperature and high pressure conditions, has a high colloid utilization rate and a low cost, and can accurately control the thickness and quality of the thin film by adjusting parameters such as the rotation speed, coating time and concentration of the coating liquid. The film thickness can be accurately controlled between 30nm and 2000nm with good repeatability; less coating material is required, and the material utilization rate is high. For layer-by-layer coating of multiple layers, the secondary dissolution of the previous layer can be reduced.
[0018] 4. The titanium dioxide film prepared by the present invention has strong physical and chemical stability, close bonding with the substrate, high piezoelectric constant, and outstanding catalytic performance, and has broad application prospects in the fields of sensors, environmental pollution control, and artificial intelligence. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 is the X-ray diffraction pattern of the TiO2 film prepared in Example 1, wherein b is an enlarged view of a.
[0020] Figure 2 This is a scanning electron microscope image of the TiO2 film prepared in Example 1.
[0021] Figure 3 This is a graph showing the degradation rate of Rhodamine B by the TiO2 film prepared in Example 1 under pyroelectric conditions. DETAILED DESCRIPTION
[0022] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments, but the protection scope of the present invention is not limited to these embodiments.
[0023] Example 1
[0024] Step 1: Preparation of TiO2 sol
[0025] 11 mL of tetrabutyl titanate and 17 mL of anhydrous ethanol were mixed evenly and stirred magnetically to obtain solution A. 17 mL of deionized water, 8 mL of glacial acetic acid, and 2 mL of nitric acid were mixed, and 2 g of sodium 1-octane sulfonate was added and stirred magnetically to obtain solution B. 28 mL of solution B was dripped dropwise into 27 mL of solution A and stirred for 30 min to obtain a uniform light yellow transparent TiO2 sol.
[0026] Step 2: Preparation of TiO2 thin film
[0027] Ultrasonic cleaning of P-type (100) crystal silicon wafer in deionized water for 5 minutes, then ultrasonic cleaning in anhydrous ethanol for 5 minutes, then drying the cleaned silicon wafer, placing the silicon wafer on the turntable of the spin coater with tweezers, taking 5mL of TiO2 sol and dropping it in the center of the silicon wafer, turning on the power of the spin coater, setting the low speed to 350rpm, spinning for 15s, and the high speed to 3000rpm, spinning for 30s. After the spin coating is completed, the silicon wafer is first dried and placed in a drying oven, and dried at 170℃ for 20min. After cooling to room temperature, take it out and carry out the next coating, a total of 5 times of spin coating. The spin-coated silicon wafer is placed in a muffle furnace and annealed at 850℃ for 90min to finally obtain a TiO2 film based on the silicon wafer.
[0028] Depend on Figure 1 It can be seen that all the main diffraction peaks of the TiO2 film can well indicate the standard patterns of Si (PDF#80-0018) and TiO2 (PDF#88-1173), which indicates that the solid film is formed as anatase phase at the single crystal silicon. Figure 1 In (a), we can see two strong peaks around 69°, corresponding to the crystal planes (400) and (301), respectively. All diffraction peaks correspond to the standard card PDF#80-0018 for Si and the standard card PDF#88-1173 for TiO2. Figure 2It can be seen that the surface of the TiO2 film is highly flat and uniform. After testing, the piezoelectric constant (d 33 ) can reach 2200pC / N.
[0029] The TiO2 film obtained in this embodiment was placed in an ultrasonic cleaner and water was added. The ultrasonic wave was modulated to a low-frequency mode. After continuous ultrasonication for 12 hours, there was no shedding of the film on the surface of the silicon wafer. When ultrasonication was continued, there was still no shedding of the film, indicating that the TiO2 film was tightly bonded to the silicon wafer substrate.
[0030] Comparative Example 1
[0031] In step 1 of Example 1, sodium 1-octane sulfonate was not added, and the other steps were the same as those of Example 1 to prepare a TiO2 film with a silicon wafer as the substrate. The piezoelectric constant (d 33 ) is 2100pC / N, which is not much different from Example 1. However, when the obtained TiO2 film is placed in an ultrasonic cleaner and water is added, the ultrasonic wave is modulated to a low-frequency mode, and the ultrasonic wave is continuously used for 12 hours, a complete transparent film can be seen on the water surface, indicating that the TiO2 film is completely detached from the silicon wafer substrate. It can be seen that whether or not to add sodium 1-octane sulfonate has an important influence on whether the formed TiO2 film is tightly bonded to the substrate.
[0032] Comparative Example 2
[0033] In step 2 of Example 1, the P-type (100) crystal face silicon wafer used was replaced with a common silicon wafer, and the other steps were the same as in Example 1 to prepare a TiO2 thin film with the silicon wafer as the substrate. The piezoelectric constant (d 33 ) is 100pC / N. The obtained TiO2 film was placed in an ultrasonic cleaner and water was added. The ultrasonic wave was modulated to a low frequency mode. After 12 hours of continuous ultrasonication, a complete transparent film could be seen on the water surface, indicating that the TiO2 film was completely detached from the silicon wafer substrate. It can be seen that the choice of substrate not only affects the piezoelectric constant of the TiO2 film, but also affects the bonding strength between the TiO2 film and the substrate.
[0034] Example 2
[0035] Step 1: Preparation of TiO2 sol
[0036] 10 mL of tetrabutyl titanate and 20 mL of anhydrous ethanol were mixed evenly and stirred magnetically to obtain solution A. 20 mL of deionized water, 10 mL of glacial acetic acid and 2 mL of nitric acid were mixed, and 3 g of sodium 1-octane sulfonate was added and stirred magnetically to obtain solution B. 32 mL of solution B was dripped dropwise into 30 mL of solution A and stirred for 30 min to obtain a uniform light yellow transparent TiO2 sol.
[0037] Step 2: Preparation of TiO2 thin film
[0038] Ultrasonic clean the P-type (100) crystal silicon wafer in deionized water for 5 minutes, then ultrasonic clean it in anhydrous ethanol for 5 minutes, then dry the cleaned silicon wafer, place the silicon wafer on the turntable of the spin coater with tweezers, take 5mL of TiO2 sol and drop it in the center of the silicon wafer, turn on the power of the spin coater, set the low speed to 500rpm, spin coat for 15s, and the high speed to 3500rpm, spin coat for 30s. After the spin coating is completed, first dry the silicon wafer and put it in a drying oven, and dry it at 180℃ for 30min. After cooling to room temperature, take it out and carry out the next coating, and spin coat it 5 times in total. Put the spin-coated silicon wafer into a muffle furnace and anneal it at 900℃ for 60min to finally obtain a TiO2 film with a silicon wafer as the substrate. After testing, the piezoelectric constant (d 33 ) is 2170 pC / N. After the TiO2 film obtained in this embodiment was ultrasonicated in deionized water for 12 hours, the film on the silicon wafer surface did not fall off. After the ultrasonication was continued, the film still did not fall off, indicating that the TiO2 film was tightly bonded to the silicon wafer substrate.
[0039] Example 3
[0040] Step 1: Preparation of TiO2 sol
[0041] 10 mL of tetrabutyl titanate and 15 mL of anhydrous ethanol were mixed evenly and stirred magnetically to obtain solution A. 15 mL of deionized water, 5 mL of glacial acetic acid and 1 mL of nitric acid were mixed, and 1.5 g of sodium 1-octane sulfonate was added and stirred magnetically to obtain solution B. 21 mL of solution B was dripped dropwise into 25 mL of solution A and stirred for 30 min to obtain a uniform light yellow transparent TiO2 sol.
[0042] Step 2: Preparation of TiO2 thin film
[0043] Ultrasonic clean the P-type (100) crystal silicon wafer in deionized water for 5 minutes, then ultrasonic clean it in anhydrous ethanol for 5 minutes, then dry the cleaned silicon wafer, place the silicon wafer on the turntable of the spin coater with tweezers, take 5mL of TiO2 sol and drop it in the center of the silicon wafer, turn on the spin coater power, set the low speed to 300rpm, spin coat for 20s, and the high speed to 2500rpm, spin coat for 30s. After the spin coating is completed, first dry the silicon wafer and put it in a drying oven, and dry it at 150℃ for 60min. After cooling to room temperature, take it out and carry out the next coating, and spin coat it 5 times in total. Put the spin-coated silicon wafer into a muffle furnace and anneal it at 800℃ for 90min to finally obtain a TiO2 film with silicon wafer as the substrate. After testing, the piezoelectric constant (d 33) is 2250 pC / N. After the TiO2 film obtained in this example was ultrasonically treated in deionized water for 12 hours, the film on the silicon wafer surface did not fall off. After the ultrasonic treatment was continued, the film still did not fall off, indicating that the TiO2 film was tightly bonded to the silicon wafer substrate.
[0044] In order to demonstrate the beneficial effects of the present invention, taking the organic dye Rhodamine B as an example, the TiO2 film based on Si prepared in Example 1 was used to carry out degradation experiments under photocatalytic, piezoelectric catalytic and pyroelectric conditions, respectively. The specific methods are as follows:
[0045] 100 mL of 5 mg / L Rhodamine B aqueous solution was injected into a sealed, light-transmitting glass container, and the prepared 4-inch silicon-based TiO2 film was immersed in the Rhodamine B aqueous solution, and photocatalytic degradation of Rhodamine B was carried out under natural light. Samples were taken after 24 hours of reaction, and the results showed that the degradation rate of Rhodamine B was 96%.
[0046] 100 mL of 5 mg / L Rhodamine B aqueous solution was injected into a sealed, light-proof glass container, and a 4-inch silicon wafer-based TiO2 film was immersed in the Rhodamine B aqueous solution. The glass container was placed in an ultrasonic cleaner, water was added to the ultrasonic cleaner, and the ultrasonic wave was modulated to a low-frequency mode to perform piezoelectric catalytic degradation of Rhodamine B. Samples were taken after 3 hours of reaction, and the results showed that the degradation rate of Rhodamine B was 56%.
[0047] Pour 100mL of 5mg / L Rhodamine B aqueous solution into a sealed, light-proof glass container, immerse the prepared 4-inch silicon-based TiO2 film in the Rhodamine B aqueous solution, place the glass container on a programmable temperature controller, and set the temperature control program as follows: 3min from room temperature to 60℃, then 22min from 60℃ to 10℃, with 25min as a cycle, and perform pyroelectric degradation of Rhodamine B under cyclic temperature control. The results are shown in the figure. Figure 3. After 12h, the degradation rate of Rhodamine B was 48%. It can be seen from the experimental results of the degradation of Rhodamine B that the amount of TiO2 film used in the experiment is very small, but the degradation effect is significant, which further highlights the high efficiency and economy of the TiO2 film prepared by the present invention. Low dosage means that in practical applications, material consumption can be reduced, costs can be reduced, and efficient degradation performance can be maintained. The TiO2 film of the present invention has extremely high efficiency and practicality in the field of photocatalysis, and can significantly reduce organic pollutants in aqueous solution in a short time. And it can also effectively degrade organic pollutants under ultrasonic conditions, showing its application potential in the field of piezoelectric catalysis. Under pyroelectric conditions, although the degradation rate is slightly lower than that of photocatalysis and piezoelectric catalysis, it also shows the catalytic activity of TiO2 film under temperature change conditions. TiO2 film shows good degradation effect under different catalytic conditions, whether under light, ultrasound or temperature change conditions, it can effectively degrade Rhodamine B, which shows its adaptability and stability under different environmental conditions.
Claims
1. A method for preparing a high-performance titanium dioxide film, characterized in that: The preparation method comprises the following steps: Step 1: Preparation of TiO2 sol Tetrabutyl titanate and anhydrous ethanol are mixed evenly, and solution A is obtained after magnetic stirring; deionized water, glacial acetic acid and nitric acid are mixed, sodium 1-octane sulfonate is added and solution B is obtained after magnetic stirring; solution B is dripped into solution A drop by drop, and stirred evenly to obtain TiO2 sol; Step 2: Preparation of TiO2 thin film The P-type (100) silicon wafer is ultrasonically cleaned in deionized water and anhydrous ethanol in turn and then dried. The TiO2 sol obtained in step 1 is spin-coated on the silicon wafer. After drying, the spin coating is repeated 3 to 5 times. The spin-coated silicon wafer is annealed to obtain a TiO2 film based on the silicon wafer.
2. The method for preparing a high-performance titanium dioxide film according to claim 1, characterized in that: In step 1, the volume ratio of tetrabutyl titanate, anhydrous ethanol, deionized water, glacial acetic acid and nitric acid is 1:1.5-2:1.5-2:0.5-1:0.1-0.
2.
3. The method for preparing a high-performance titanium dioxide film according to claim 1 or 2, characterized in that: In step 1, the mass-volume ratio of the sodium 1-octane sulfonate to tetrabutyl titanate is 0.15-0.3 g:1 mL.
4. The method for preparing a high-performance titanium dioxide film according to claim 1, characterized in that: In step 2, the drying temperature is 150-180° C., and the drying time is 20-60 min.
5. The method for preparing a high-performance titanium dioxide film according to claim 1, characterized in that: In step 2, the spin coating is firstly carried out at a rotation speed of 300 to 500 rpm for 10 to 20 s, and then at a rotation speed of 2500 to 3500 rpm for 20 to 30 s.
6. The method for preparing a high-performance titanium dioxide film according to claim 1, characterized in that: In step 2, the annealing temperature is 800-900° C., and the annealing time is 60-90 min.